RETRACTED: Does Capital Account Liberalization and Foreign Banks Ownership Lead to Income Disparity? An Analysis of BRICS Economies - Sabri, Rabia; Mujahid, Hira; Jumani, Nayab (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of the study is to evaluate the impact of capital account liberalization and foreign bank ownership on income inequality. In this study, we have analyzed BRICS countries. In this study, we have used an unbalanced panel dataset. The timeline was 1991-2020, and the BRICS countries (Brazil, Russia, India, China, and South Africa) were analyzed. To measure the data on capital account liberalization, we have used the KAOPEN index. We used income inequality as the independent variable in the study, and we measured it through Gini Coefficient. At the same time, the capital account liberalization is taken as the dependent variable and measured it through the KAOPEN index. The author analyzed per capita income, unemployment rate, inflation, and population growth as controlled variables. In robustness analysis, institutional quality variables such as corruption and government stability ratings were included. The study found that sustainable capital account liberalization and foreign banks ownership could help to reduce income inequality.